The Women and Modern Society in â€œSex and the Cityâ€: A Sociological Approach - Kerpaci, Kalie; Hoxha, Denata; Kuka, Martin (Mediterranean Journal of Social Sciences, 2012)
This article is an attempt to analyze social phenomena represented through the daily discourse of four single white,intelligent and rich New York women in their thirties in the central of the sitcom â€œSCâ€(hereafter SC). Main issue of this article is todiscover the social messages prevailed in this sitcom such as sexual release, the right of the woman to make her choices whichconstitutes main issues of the third wave of feminist movement. SC provides the viewer with real female conversations aboutquestions of sex in a way that has typically been a male discourse on television. Using different sociological theoreticalreflections on modernity we try to explain the changes shaping the individual and the family relations, occurring within themodern society. Through the four main characters of this sitcom, we try to present the fixation of women in modernity onshopping, fashion, body and sexual relationships and how the kinship relations are replaced by those of friends. SC givesemphasis on advertising latest fashions and restaurants, night clubs, coffee shops in certain places of New York City.